The second Karabakh war in the context of covering events in the Russian media and expert evaluations - Dunamalyan, Norayr; Sarkisyan, Hovhannes (YSU Journal of International Affairs, 2021)
This article is based on an expert survey conducted during the Second Artsakh War. The main goal was to understand the Russian public discourse on the Artsakh issue, separating the opinions presented in the social surveys, the media field and the assessments of Russian experts. It is interesting to compare the general position of the Russian leadership on the Artsakh war, and analyze its impact on the state propaganda.